Atopic dermatitis. Interdisciplinary diagnostic and therapeutic recommendations of the Polish Dermatological Society, Polish Society of Allergology, Polish Pediatric Society and Polish Society of Family Medicine. Part I. Prophylaxis, topical treatment and phototherapy - Nowicki, Roman; Trzeciak, Magdalena; Kaczmarski, Maciej; Wilkowska, Aleksandra; Czarnecka-Operacz, Magdalena; Kowalewski, Cezary; Rudnicka, Lidia; Kulus, Marek; Mastalerz-Migas, Agnieszka; Peregud-Pogorzelski, Jarosław; Sokołowska-Wojdyło, Małgorzata; Śpiewak, Radosław; et al. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Atopic dermatitis is a chronic and recurrent inflammatory dermatosis with concomitant intensive pruritus, and is diagnosed both in children and adults. Atopic dermatitis-patients are predisposed to have bacterial, viral and fungal skin infections; they also suffer from an increased risk of developing food allergies (especially, at an infantile age), allergic rhinitis, or bronchial asthma (a so-called atopic march). Currently, an increasing atopic dermatitis incidence constitutes a serious medical problem that regards not only dermatology and allergology, but also paediatrics, and family medicine. The basis for atopic dermatitis treatment and prophylaxis is restoration of epidermal barrier functions by means of tailored emollients. Atopic dermatitis therapies should effectively eliminate clinical symptoms of the disease, prevent exacerbations as well as complications, and improve patients’ quality of life.